Understanding spatial-temporal travel demand of free-floating bike sharing connecting with metro stations. (November 2021) - Yu, Senbin; Liu, Gehui; Yin, Congru
Highlights: Propose a physics-rooted approach to investigate spatial-temporal demand of bike-and-ride. Find spatial scaling relationship between trips of bike-and-ride and the distance to the city center. Construct a fine time granularity to investigate the travel demand of bike-and-ride. Discuss the distinct characteristics of scale-free behavior in different regions of the city. Summarize the practical implications and applications drawn from the empirical findings. Abstract: Free-floating bike sharing usage for metro access provides a decent solution to the first- and last-mile problem. A fundamental and still open problem is the spatial and temporal regularities of bike sharing usage integrated with metro stations, which are crucial to achieve a seamless connection and provide an efficient transport system. In this paper, we conduct the usage of bike-and-ride in Beijing as an example to address this issue from macro-level and micro-level perspectives. First, the macroscopic usages, including distinct characteristics of time-varying trips and scaling relationships of spatial distribution, are explored in urban and suburban areas. Then, by adequately deconstructing temporal-spatial trips of bike-and-ride, the bike sharing usage is revealed to follow a power-law distribution with different exponents on weekdays and weekends. Our results suggest that scale-free behaviors for microcosmic travel demand exist across the city. These vital phenomena switch within the same region on different time ranges such as morning and evening peaks but similar scaling relations on different days. The findings improve our understanding of usage patterns and demand distribution of this emerging transport mode and supply an indication of the dynamic deployment of the free-floating bike sharing integrating with the mass transit system.